2008
DOI: 10.1590/s0100-204x2008000400010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and pathogenicity of isolates of Beauveria spp. to fall armyworm

Abstract: -The objective of this work was to evaluate the pathogenicity of 24 Beauveria isolates to Spodoptera frugiperda larvae, and characterize them molecularly through rDNA-ITS sequencing and RAPD markers. Sequencing of rDNA-ITS fragments of 570 bp allowed the identification of isolates as B. bassiana or B. brongniarti by sequence comparison to GenBank. Sixty seven polymorphic RAPD fragments were capable to differentiate 20 among 24 Beauveria isolates, grouping them according to the derived host insect and to pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
2
11
1
3
Order By: Relevance
“…The proportion of monomorphic loci between the most virulent isolates was low (16.2%). Although some studies have reported a relationship between the molecular profile of isolates of entomopathogenic fungi and their initial host (CARNEIRO et al, 2008;OLIVEIRA et al, 2011) or geographical origin (FERNANDES et al, 2009), such a relationship was not found in the present study, either through analysis of the rDNA-ITS region or the groups generated via RAPD analysis, similar to the results of Becerra-Velásquez et al (2007) and Mendonça et al (2012).…”
Section: Molecular Characterizationcontrasting
confidence: 49%
“…The proportion of monomorphic loci between the most virulent isolates was low (16.2%). Although some studies have reported a relationship between the molecular profile of isolates of entomopathogenic fungi and their initial host (CARNEIRO et al, 2008;OLIVEIRA et al, 2011) or geographical origin (FERNANDES et al, 2009), such a relationship was not found in the present study, either through analysis of the rDNA-ITS region or the groups generated via RAPD analysis, similar to the results of Becerra-Velásquez et al (2007) and Mendonça et al (2012).…”
Section: Molecular Characterizationcontrasting
confidence: 49%
“…Furthermore, the informational presence of S. frugiperda in homeopathic preparation may have been based on the homeopathy principles, a factor to stimulate the growth of fungus that is pathogenic to this insect (Carneiro et al, 2008).…”
Section: Homeopathic Drugsmentioning
confidence: 99%
“…The number of bands generated by each primer differed from 4 (OPA09) to 13 (OPA03 and OPQ01), with an average of 5.3 bands per primer. The size of the bands varied from 300 (OPZ19) to 3800 (OPA 13) base pairs (Carneiro et al, 2008).…”
Section: Resultsmentioning
confidence: 99%